A Study of Luminance and Visual Attention Patterns in Tourist Photography at Fairy Cave Sarawak - Rosli, Saiful Azlan; Ahmad, Azmir; Jamaluddin, Siti Aisyah Afiqah; Azman, Nur Ain Noor; Chen, Ai-Hong; Jamil, Azhar Abd (Journal of Health Science and Medical Research, 2024)
Objective: Visual attention involves complex interaction between the cognitive and surrounding environment. Eye movement and light uniformity be the important factor that influence visual attention. Digital photos emit light compared the conventional photos. It would be advantageous to investigate and comprehend the significance of the amount of light that enters the eye, known as luminance. The primary objective of this study was to conduct luminance light and visual attention analysis using scenery images captured from tourist spots located in Fairy Cave, Sarawak. Material and Methods: There were 3 parts in this study. Part One: convenient sampling was employed to recruit three adults as tourist photographers to capture images at four pre-selected tourist locations in Fairy Cave, Sarawak. Part Two: a total of 17 photographs were chosen from a pool of forty photographs for the purpose of conducting research on the luminance and visual activity. The luminance analysis evaluated the luminosity emitted by the digital display. The luminous properties were assessed using the CA-2500 2D Colour Analyzer manufactured by Konica Minolta in Japan. The brightness profile of the images is obtained by calculating the Michelson luminance. Part Three: the Dikablis eye tracker was utilised to test the visual attention via eye tracking pattern of a sample of thirty-six adults aged 18 to 40 years. The researchers recorded and examined the total amount and duration of the fixation eye movement. Results: The 3 photographers that were recognised exhibited both similarities and differences in their photographic skills and preferences. Nevertheless, this was not incorporated into our investigation of visible spectrum light. The observed difference in brightness profiles among the images was found to be statistically insignificant (p-value>0.05). Our study on eye-tracking behaviour in adults revealed significant variations in the total number of fixations (p-value<0.05). Conclusion: Our findings provide valuable insights into the interplay between environmental lighting conditions and visual attention in this unique natural setting. Despite having various angle preferences, layperson photographers appear to engage in the same visible light spectrum. Our study indicates that when investigating preferences using the visual attention component, it is important to consider the total count of fixations. Additional investigation could entail the examination of professional photographers’ photography.